Media literacy in ‘Big Kitchen (1952)’ historical documentary - Ali, Mohd Nor Shahizan; Fleming, Dan; Salman, Ali; Lyndon, Novell (2017)
Gen Y as a whole have different abilities in interpretation on the text media. Therefore, each issue necessary media texts not to cause confusion in the interpretation of the message.In line with the rapid pace of information technology to make all information more easily accessible lead the audience (Gen Y) became more confused in making the interpretation of the meaning; depending on their literacy level.The importance of media literacy should be considered in the process of reading on historical documentary.This article explores the interpretation of Gen Y at the Institute of Higher Learning on the historical documentary ‘Big Kitchen (1952)’ work of Malay Film Unit.A focus group discussion was conducted on seven informants selected.The discussion focuses on the literacy aspect and the overall interpretation of the historical documentary narrative as a message.A historical documentary has given rise to different interpretations among them.The results supports that the Gen Y who totally exposed to the media environment in everyday life able to understand the narrative of the historical documentary.The results showed that the transformation of social technologies and the impact of extensive and open information have influenced the interpretation of Gen Y.